FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN ABSOLUT DI KABUPATEN BARITO KUALA - HERLY MEILINDA (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This research was conducted to analyze the factors that influence absolute poverty in Barito Kuala Regency. One of the causes of the still high population is poor due to the rapid population growth. The still high number of poor people is indicated by a large number of poor people, economic growth, high unemployment rate, and low level of education.This research is located in Barito Kuala District, as well as data source used is secondary data consisting of time series data during the period 2004 to 2015 which the data is analyzed using multiple linear regression models. To find out whether economic growth, open unemployment rate, population growth and education level affect the number of poor people in Barito Kuala District. The results of this study indicate that the variables of the open unemployment rate, economic growth , and education level do not significantly affect the number of poor people, while population growth significantly influences the number of poor people.Keywords: Number of poor people, economic growth, open unemployment rate, population growth and education level.